Effect of the millennial 2.0 entrepreneurship program on the technological innovation capacity of the students at the Universidad Nacional de Cañete - Rios Rios, Segundo (2023)
It is proposed to demonstrate that the millennial 2.0 program significantly influences the technological innovation of the students of the Universidad Nacional de Cañete. It is evidenced that the lack of technical training in the millennial 2.0 entrepreneurship program prevents students from raising awareness, while the application of a test highly motivates the students of the same program, demonstrating that the training significantly influences the program. MSEs that apply strategic planning improve their financial management and have greater control of their resources and an aceptable development in the market where they operate. Technological innovation and constant training in the millennial 2.0 program produce a greater acceptance of the innovation that is given to students and future professionals in such a way that a greater adaptation in technology and student innovation is achieved in universities, this program is directly proportional to technological innovation because the more training on this program, the greater will be their acceptance and motivation to accept the new changes. The present study has a quantitative approach, for this, the survey technique was used and the virtual multifactorial questionnaire was used as an instrument, carried out on 120 students from the university of Cañete of the school of administration, accounting and administration of tourism and hospitality, which consist of four dimensions for each variable. It was obtained from this research article that in millennial entrepreneurship 2.0 the training helped to raise awareness among the students of the University of Cañete by 70% under the positive effect of the millennial 2.0 program, resulting in an increase of 27.5 % above the average acceptance level, in terms of university technological innovation, the interest of students rises up to 75.0% while the impact on teachers reaches 72.5% after receiving technological innovation training.